Associations between Online Hate Victimization and Perpetration - Sebastian Wachs; Michelle F. Wright (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung, 2021)
It is well known that victims of violence are more likely than non-victims to be perpetrators, and that perpetrators are more likely than non-perpetrators to be victims. However, the overlap between being the victim of violence and the perpetrator of violence is not well understood when it comes to online hate. An explanatory mechanism in this relationship could potentially be the use of specific coping strategies. We sought to develop a better understanding of the relationship between the victims and the perpetrators of online hate to inform effective intervention and prevention initiatives in the field of media education. Self-report questionnaires on receiving and committing online hate and on technical and assertive coping were completed by 1,480 young people between 12 and 17 years old (M = 14.21 years; SD = 1.68). Results showed that increases in being the recipient of online hate were positively related to being a perpetrator of online hate. Technical and assertive coping strategies were negatively related to perpetrating online hate. Furthermore, victims of online hate reported less instances of perpetrating online hate when they reported higher levels of technical and assertive coping strategies, and more frequent instances of perpetrating online hate when they reported lower levels of technical and assertive coping strategies. In conclusion, our findings suggest that, if they are to be effective, prevention and intervention programs that target online hate should consider educating young people in problem-focused coping strategies.